On a class of reflected AR(1) processes. (September 2016) - Boxma, Onno; Mandjes, Michel; Reed, Josh
Abstract: In this paper we study a reflected AR(1) process, i.e. a process ( Z n ) n obeying the recursion Z n +1 = max aZ n + X n, 0, with ( X n ) n a sequence of independent and identically distributed (i.i.d.) random variables. We find explicit results for the distribution of Z n (in terms of transforms) in case X n can be written as Y n − B n, with ( B n ) n being a sequence of independent random variables which are all Exp(λ) distributed, and ( Y n ) n i.i.d.; when | a |<1 we can also perform the corresponding stationary analysis. Extensions are possible to the case that ( B n ) n are of phase-type. Under a heavy-traffic scaling, it is shown that the process converges to a reflected Ornstein–Uhlenbeck process; the corresponding steady-state distribution converges to the distribution of a normal random variable conditioned on being positive.